Study of neutron spectra in a water bath from a Pb target irradiated by 250 MeV protons - 李严严 张雪荧 鞠永琴 马飞 张宏斌 陈亮 葛红林 万波 骆鹏 周斌 张艳斌 李建阳 徐俊奎 王松林 杨永伟 杨磊 (Chinese physics C, 2015)
Spallation neutrons were produced by the irradiation of Pb with 250 MeV protons. The Pb target was surrounded by water which was used to slow down the emitted neutrons. The moderated neutrons in the water bath were measured by using the resonance detectors of Au, Mn and In with a cadmium （Cd） cover. According to the measured activities of the foils, the neutron flux at different resonance energies were deduced and the epithermal neutron spectra were proposed. Corresponding results calculated with the Monte Carlo code MCNPX were compared with the experimental data to check the validity of the code. The comparison showed that the simulation could give a good prediction for the neutron spectra above 50 eV, while the finite thickness of the foils greatly effected the experimental data in low energy. It was also found that the resonance detectors themselves had great impact on the simulated energy spectra.